Improving Digital Literacy and Indonesian Language for the Indonesian Community in Malaysia - Enik Rahayu; Hendrajaya Hendrajaya; C. Susmono Widagdo; Henry Yuliamir; Nicolas Kevin Sulityawardhana; Anisa Eka Khatarina (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2025)
This study focuses on improving digital literacy and formal Indonesian language proficiency among the Indonesian diaspora community in Kampung Baru, Kuala Lumpur, Malaysia. The community faces challenges in adapting to digital technology and maintaining linguistic and cultural identity, which limits their socio-economic participation and engagement in community activities. The objective of this research is to develop and implement a community-based program that enhances digital skills while promoting national language usage and cultural preservation. The program employed a participatory and interactive approach, including workshops, hands-on practice, mentoring, role-play, and storytelling, targeting 30 participants comprising youth, MSME actors, teachers, village officials, and housewives. Pre-test and post-test evaluations, direct observation, and interviews were used to assess the impact of the program. The results show significant improvements in digital literacy, with participants demonstrating enhanced skills in e-mail usage, document sharing, e-wallet applications, and digital security awareness, with post-test gains ranging from 40% to 45%. Likewise, proficiency in formal Indonesian language, public speaking, and cultural knowledge increased by 25% to 28%, reflecting both technical and cultural skill development. The findings indicate that community-based, participatory learning integrated with cultural reinforcement effectively bridges the digital divide and strengthens linguistic identity among diaspora communities. The study concludes that such a hybrid model not only empowers participants in digital and linguistic capacities but also promotes cultural sustainability and social cohesion, offering a scalable and replicable framework for similar communities.